Effects of P2Y12 receptor antagonists beyond platelet inhibition – comparison of ticagrelor with thienopyridines. (24th February 2016) - Nylander, Sven; Schulz, Rainer
Abstract : The effect and clinical benefit of P2Y12 receptor antagonists may not be limited to platelet inhibition and the prevention of arterial thrombus formation. Potential additional effects include reduction of the pro‐inflammatory role of activated platelets and effects related to P2Y12 receptor inhibition on other cells apart from platelets. P2Y12 receptor antagonists, thienopyridines and ticagrelor, differ in their mode of action being prodrugs instead of direct acting and irreversibly instead of reversibly binding to P2Y12 . These key differences may provide different potential when it comes to additional effects. In addition to P2Y12 receptor blockade, ticagrelor is unique in having the only well‐documented additional target of inhibition, the equilibrative nucleoside transporter 1. The current review will address the effects of P2Y12 receptor antagonists beyond platelets and the protection against arterial thrombosis. The discussion will include the potential for thienopyridines and ticagrelor to mediate anti‐inflammatory effects, to conserve vascular function, to affect atherosclerosis, to provide cardioprotection and to induce dyspnea.